Interventions on Well-being, Occupational Health, and Aging of Healthcare Workers: A Scoping Review of Systematic Reviews - Marc Fadel; Yves Roquelaure; Alexis Descatha (Elsevier, 2023)
Introduction: With recent higher awareness of the necessity of improving healthcare workers' well-being, we aimed to overview systematic reviews dealing with interventions on well-being, occupational health, and aging of healthcare workers. Methods: From three databases (PubMed, Embase, and Web of Science), a scoping review of systematic reviews was carried out to determine current knowledge on interventions focused on the well-being or aging of healthcare workers. Only systematic reviews were considered, with appropriate extraction and quality evaluation. Results: Of the total of 445 references identified, 10 systematic reviews were included, mostly published since 2019. Nurses were the most frequent targets of interventions, and mental health was the main outcome described. The overall level of quality was also heterogenous, with high to low-quality reviews. Conclusions: Workers' mental health well-being was the major outcome targeted by intervention, with varying level of evidence. Further studies are needed with integrative approaches on global health and life course perspectives, with a focus on the plurality of settings, worker types, and women.